Synthesis and Characterizations of Poly(trimethylene terephthalate)-b-poly(tetramethylene glycol) Copolymers - Feng Liu; Meng Yao; Ming-tao Run (International Journal of Polymer Science)
A series of poly(trimethylene terephthalate)-b-poly(tetramethylene glycol) (PTT-PTMEG) copolymers were synthesized by two-step melt-polycondensation. The copolymers were characterized by using Fourier transform infrared spectroscopy (FTIR), 1H NMR spectroscopy, rheometer, differential scanning calorimetry (DSC), polarized optical microscopy (POM), thermal gravimetric analysis (TGA), and mechanical properties. The results suggest that by increasing the flexible PTMEG contents from 0% to 60 wt%, the copolymers show decreased glass transition temperatures, melting points, melt-crystallization temperatures, hardness, tensile strength, thermostability, and smaller spherulites dimensions; however it has much increased impact strength and elongation at breaking point. Compared with commercial poly(butylene terephthalate) (PBT)-type TPEE with 25 mol% flexible segments, PTT-type TPEE having 25 mol% flexible segments has a lower glass transition temperature, melting point, crystallization temperature, and much lower tensile strength although it has a much higher impact strength than that of PBT-type TPEE, and it is not suitably used as a commercial TPEE.